Evaluation of neurologically symptomatic and asymptomatic patients in childhood Wilson's disease with central nervous system involvement: A retrospective observational study (Annals of Medical Research, 2023)
Aim: The aim was to evaluate the clinical and laboratory characteristics of children with Wilson's disease (WD) with and without neurological presentation with abnormalities on brain magnetic resonance imaging (MRI) and to describe the relationship of these observations with disease severity and functional outcome and their impact on prognosis.Materials and Methods: Demographic, neuropsychiatric findings, laboratory, disease severity and functional results of 48 children with neurologically symptomatic and asymptomatic WD were evaluated retrospectively.Results: A significant positive correlation was found between the neurologic symptom score and functional outcome in WD with neurological presentation (p
Keywords: Wilson's disease; Hepatology; Neurology; Pediatric practice; Functional outcome